Transportation Planning Studies for Socio-Economic Development of Depressed Sub-Regions: A Review - Mir Aftab Hussain Talpur; Tauha Hussain Ali; Imtiaz Ahmed Chandio; Fahad Ahmed Shaikh (Mehran University Research Journal of Engineering and Technology, 2018)
Transport sector can be considered as a backbone of the national and regional economies. Well-arranged transportation facilities are essential for the movement of people and goods, which can make nations agile and strong to face ever-increasing global and local socioeconomic problems. However, most of the developing countries were facing acute transport-related problems, i.e. absence of transport policies, inaccessibility, the proper road network hierarchy and unavailability of low-cost transportation services, especially for rural dwellers. Hence, the aim of this research is to propose policy implications by reviewing suitable literature associated with regional transportation planning, which can be essential to upsurge accessibility standards and abolish the transport-related problems of the rural sub-regions of developing countries. This research article is intended for the planned development and socioeconomic well-being of depressed sub-regions, which are struggling with the problem of transportation inaccessibility over the years. It was found that accessibility is a dominant element of transportation studies in rural sub regions, if addressed by the concerned authorities or planning agencies; the deprived sub-regions can flourish and prosper with the passage of time.